Parental Gifts To Children In The Karang Tinggi Community : An Analysis Based On Al-Shatibi's Maqashid Al-Shariah - Rahim, Abdur; A. K Husein, Moh Hidayatullah; Fajrin, Hari (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2026)
Abstracts: This study examines the practice of parental gifts to children in the community of Karang Tinggi Subdistrict, Central Bengkulu Regency, from the perspective of Maqashid al-Shariah. In Islamic law, a gift is a tabarru’ contract aimed at providing benefit to the recipient without compensation, as well as serving as a means of strengthening family social and economic ties. However, in community practice, gifts are often understood not only as voluntary giving but also as a mechanism for distributing inheritance assets while the parents are still alive. This study employs a qualitative method with a normative-empirical approach. Data were collected through interviews, observations, and documentation, and analysed using the Maqashid al-Syariah perspective according to Abu Ishaq al-Shatibi. The results of the study indicate that the practice of gift-giving is carried out as an expression of affection, economic support, and an effort to avoid inheritance disputes. However, in its implementation, patterns of giving that are unilateral, unequal, and not fully based on family consultation are still observed. From the perspective of Maqashid al-Syariah, these gift-giving practices are not yet fully aligned with the objectives of Sharia, particularly regarding the protection of wealth (hifz al-mal) and lineage (hifz al-nasl). Gift-giving practices are more often categorised under secondary needs (hajiyat) rather than primary needs (dharuriyat), thereby still harbouring the potential for injustice and family conflict. Therefore, a more comprehensive understanding of the concept of gifts in accordance with Sharia is needed so that their implementation remains within the framework of justice and public interest.Keywords: Gift; Parents and Children; Maqashid al-Shariah; Islamic Inheritance Law; Islamic law. Abstrak : Penelitian ini membahas praktik hibah orang tua kepada anak di masyarakat Kecamatan Karang Tinggi, Kabupaten Bengkulu Tengah, dalam perspektif Maqashid al-Syariah. Hibah dalam hukum Islam merupakan akad tabarru’ yang bertujuan memberikan manfaat kepada penerima tanpa imbalan, serta menjadi sarana penguatan hubungan sosial dan ekonomi keluarga. Namun, dalam praktik masyarakat, hibah sering dipahami tidak hanya sebagai pemberian sukarela, tetapi juga sebagai mekanisme pembagian harta warisan semasa orang tua masih hidup. Penelitian ini menggunakan metode kualitatif dengan pendekatan normatif-empiris. Data diperoleh melalui wawancara, observasi, dan dokumentasi, kemudian dianalisis menggunakan perspektif Maqashid al-Syariah menurut Abu Ishaq al-Shatibi. Hasil penelitian menunjukkan bahwa praktik hibah dilakukan sebagai bentuk kasih sayang, dukungan ekonomi, dan upaya menghindari sengketa waris. Akan tetapi, dalam pelaksanaannya masih ditemukan pola pemberian yang bersifat sepihak, tidak merata, serta tidak sepenuhnya berdasarkan musyawarah keluarga. Ditinjau dari Maqashid al-Syariah, praktik hibah tersebut belum sepenuhnya selaras dengan tujuan syariat, khususnya dalam aspek perlindungan harta (hifz al-mal) dan keturunan (hifz al-nasl). Praktik hibah lebih banyak berada pada tingkat kebutuhan sekunder (hajiyat) dibandingkan dengan kebutuhan primer (dharuriyat), sehingga masih mengandung potensi ketidakadilan dan konflik keluarga. Oleh karena itu, diperlukan pemahaman yang lebih komprehensif mengenai konsep hibah yang sesuai syariat agar pelaksanaannya tetap berada dalam koridor keadilan dan kemaslahatan.Kata kunci: hibah, orang tua-anak, Maqashid al-Syariah, Karang Tinggi, hukum Islam.